2021
DOI: 10.3389/fcell.2020.620543
|View full text |Cite
|
Sign up to set email alerts
|

Non-neuronal Role of Acetylcholinesterase in Bone Development and Degeneration

Abstract: Acetylcholinesterase (AChE), an enzyme catalyzing the degradation of acetylcholine, plays an important suppressive role in the cholinergic regulation by terminating the action of acetylcholine. The expression of acetylcholinesterase and other cholinergic components is not restricted to only brain and nerve tissues but can also be found in non-neuronal tissues like the immune system and bone tissue. Primary identification of these components has been achieved. However, the information about their specific funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 84 publications
0
23
0
Order By: Relevance
“…And under the influence of the work of O. sanctum leaves were inhibit the acetylcholinesterase enzyme, and then the accumulation of acetylcholine occurs, and consequently, an imbalance occurs in the pulsating system of muscle cells, causing muscle spasms of the insect. In addition to the presence of flavonoids, they affect the respiratory system, affecting the breathing process, which leads to the death of the insect [28].…”
Section: Resultsmentioning
confidence: 99%
“…And under the influence of the work of O. sanctum leaves were inhibit the acetylcholinesterase enzyme, and then the accumulation of acetylcholine occurs, and consequently, an imbalance occurs in the pulsating system of muscle cells, causing muscle spasms of the insect. In addition to the presence of flavonoids, they affect the respiratory system, affecting the breathing process, which leads to the death of the insect [28].…”
Section: Resultsmentioning
confidence: 99%
“…During osteoclastogenesis of bone marrow macrophages an upregulation of the AChE expression has been observed. Moreover, genetic knockdown of AChE via siRNA suppressed RANKL-induced osteoclast differentiation 46 , 47 . These results suggest that the signaling interaction between AhR and AChE might be a potential therapeutic target for bone disease like osteoporosis and TMJ-OA.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, an exogenous stimulator of the cholinergic system, is also important component of cigarette smoke. Several studies reported the role of cholinergic system in the bone homeostasis in the context of osteoporosis and osteoarthritis 45 , 46 . Acetylcholine or exogenous activation via nicotine or muscarine, stimulates osteoblast proliferation and osteoclast apoptosis 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cholinergic system is an integral part of the human beings, which also plays a significant role in metabolic activities such as proliferation, apoptosis, assimilation, and dissimilation. Acetylcholine is an important neurotransmitter excrete from the cytoplasm to synaptic space through synaptic vesicles ( Luo et al, 2020 ). Nicotinic acetylcholine receptors and muscarinic acetylcholine receptors can be stimulated by free acetylcholine.…”
Section: Discussionmentioning
confidence: 99%